1999
DOI: 10.1073/pnas.96.2.715
|View full text |Cite
|
Sign up to set email alerts
|

Killing of Caenorhabditis elegans by Pseudomonas aeruginosa used to model mammalian bacterial pathogenesis

Abstract: We show that a single clinical isolate of the human opportunistic pathogen Pseudomonas aeruginosa (strain PA14), which previously was shown to be pathogenic in mice and plants, also kills Caenorhabditis elegans. The rate of PA14-mediated killing of C. elegans depends on the composition of the agar medium on which PA14 is grown. When PA14 is grown on minimal medium, killing occurs over the course of several days and is referred to as ''slow'' killing. When PA14 is grown on high-osmolarity medium, killing occurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
1,015
1
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 890 publications
(1,074 citation statements)
references
References 41 publications
26
1,015
1
3
Order By: Relevance
“…We have observed that BCAM0224 gene expression elicited great changes for cells grown under environmental conditions that mimic the altered microenvironment of the CF lungs. Similar to our work, other studies on CF pathogens exposed to high osmolar conditions have shown a dramatic enhancement of the expression levels of other virulence genes, either from B. cenocepacia (Tomich & Mohr, 2004;Bhatt & Weingart, 2008) or Pseudomonas aeruginosa (Tan et al, 1999). Based on these observations, we speculate that expression of BCAM0224 may play a role in the virulence of B. cenocepacia when it infects CF patients.…”
Section: Discussionsupporting
confidence: 78%
“…We have observed that BCAM0224 gene expression elicited great changes for cells grown under environmental conditions that mimic the altered microenvironment of the CF lungs. Similar to our work, other studies on CF pathogens exposed to high osmolar conditions have shown a dramatic enhancement of the expression levels of other virulence genes, either from B. cenocepacia (Tomich & Mohr, 2004;Bhatt & Weingart, 2008) or Pseudomonas aeruginosa (Tan et al, 1999). Based on these observations, we speculate that expression of BCAM0224 may play a role in the virulence of B. cenocepacia when it infects CF patients.…”
Section: Discussionsupporting
confidence: 78%
“…In the current review, we focus on the model nematode Caenorhabditis elegans, which has become a central model organism for studying the genetics of invertebrate immunity. First work in this field was published in 1999 [4,5]. Since then, the nematode's response to a variety of pathogens has been assessed.…”
Section: Brief Overview Of the Caenorhabditis Elegans Immune Systemmentioning
confidence: 99%
“…The C. elegans fast killing assays (Tan et al, 1999) Non-motile individuals were considered as dead, and the killing percentage was calculated as the ratio between dead and total C. elegans individuals.…”
Section: Tablementioning
confidence: 99%